Medidas de prevención en el manejo de la enfermedad del mal de panamá (Fusarium oxysporum R4T) en el cultivo de banano - Arias Aguirre, Aurelio Rufino (2021)
Banana is the fourth most important food crop in the world, its commercialization worldwide is produced in more than 1000 varieties of banana, reporting in 2019 a world production of 115.70 million tons. The world production of bananas is threatened by the rapid dispersal of the phytopathogenic fungus, Fusarium oxysporum R4T, which has the capacity to cause in Cavendish clones, the disease known as banana wilt or panama disease, races 1 and 2, where the Cavendish clones show resistance to such races. This pathogen is easily spread through the movement of infected planting material and banana residues. It spreads through the soil, in contact with planting implements and vehicles. The infected materials together with the spores of the pathogen are transported to the drainage channels by rainwater and through irrigation water these spores infect new areas of agricultural interest. The information obtained was carried out by means of the analysis, synthesis and summary technique, in order for the reader to know about the importance of preventive measures in the management of the disease Panama disease (F. oxysporum R4T) in cultivation. banana. For the above detailed it was determined that phytosanitary control measures are established by the Phytosanitary Surveillance Agency of each country, to prevent the entry of any quarantine pest, in the case of F. oxysporum f. sp. cubense RT4, which must be strategically applied to mitigate a significant impact on export banana production.